2006
DOI: 10.1021/bp0601241
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of l‐Homophenylalanine by Whole Cells of Recombinant Escherichia coli Expressing l‐Aminoacylase and N‐Acylamino Acid Racemase Genes from Deinococcus radiodurans BCRC12827

Abstract: L-Homophenylalanine (l-HPA) is a chiral unnatural amino acid used in the synthesis of angiotensin converting enzyme inhibitors and many pharmaceuticals. To develop a bioconversion process with dynamic resolution of N-acylamino acids for the l-HPA production, N-acylamino acid racemase (NAAAR) and l-aminoacylase (LAA) genes were cloned from Deinococcus radiodurans BCRC12827 and expressed in Escherichia coli XLIBlue. The recombinant enzymes were purified by nickel-chelate chromatography, and their biochemical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…lurida DSM43134, and Amycolatopsis azurea CCRC13413 have the ability to catalyze racemization of N-acylamino acids [17,19,20]. We found that D. radiodurans NAAAR exhibited higher racemization activity to N-acetyl-HPA [9] than to N-carbamoyl-HPA. We have determined the crystal structure of D. radiodurans NAAAR and found that residues Phe 26 and Phe 30 in lid region form a van der Waals interaction to N-acetyl group of N-acetyl-Lglutamine [15].…”
Section: Racemization Activities Of Naaar To Ncarbamoylamino Acidsmentioning
confidence: 81%
See 2 more Smart Citations
“…lurida DSM43134, and Amycolatopsis azurea CCRC13413 have the ability to catalyze racemization of N-acylamino acids [17,19,20]. We found that D. radiodurans NAAAR exhibited higher racemization activity to N-acetyl-HPA [9] than to N-carbamoyl-HPA. We have determined the crystal structure of D. radiodurans NAAAR and found that residues Phe 26 and Phe 30 in lid region form a van der Waals interaction to N-acetyl group of N-acetyl-Lglutamine [15].…”
Section: Racemization Activities Of Naaar To Ncarbamoylamino Acidsmentioning
confidence: 81%
“…In the previous report, we have found that the NAAAR from D. radiodurans has high racemization activity toward chiral Nacetyl-homophenylalanine [9]. The NAAAR from Amycolatopsis sp.…”
Section: Racemization Activities Of Naaar To Ncarbamoylamino Acidsmentioning
confidence: 92%
See 1 more Smart Citation
“…Racemases have been combined with other enzymes, such as aminomutase, acylases and amidases, in DKR reactions to provide optically pure α-hydroxyacids, amino acids and amino acid derivatives (Asano and Yamaguchi, 2005;Baxter et al, 2012;Cox et al, 2009;Hsu et al, 2006;Resch et al, 2010;Soriano-Maldonado et al, 2014;J. Wang et al, 2013;Z.-Y.…”
Section: Dynamic Kinetic Resolution Employing Biocatalytic Racemizationmentioning
confidence: 99%
“…This process presents a broad substrate scope with no expensive cofactors, excellent stereoselectivity, environmentally benign conditions, and organic solvent-tolerance, which has resulted in its application in academic and industrial chemistry. Indeed, many microbial-derived biocatalysts, including isolated enzymes and whole cells, may serve as candidates for the kinetic resolution of cyclic β-hydroxy ketones (Baxter et al 2012;Busto et al 2010;Hsu et al 2006;Kapoor and Gupta 2012;Shakeri et al 2010;Zhang et al 2013). However, in a kinetic resolution process, the ideal biocatalyst would only convert one enantiomer to the product and leave the antipode mostly unreacted.…”
Section: Introductionmentioning
confidence: 99%